Cholesterol Induces Pyroptosis and Matrix Degradation via mSREBP1-Driven Endoplasmic Reticulum Stress in Intervertebral Disc Degeneration - Yan, Jiansen; Li, Shuangxing; Zhang, Yangyang; Deng, Zhihuai; Wu, Jiajun; Huang, Zhengqi; Qin, Tianyu; Xiao, Yin; Zhou, Jie; Xu, Kang; Ye, Wei (Frontiers in Cell and Developmental Biology, 2022)
Intervertebral disc degeneration (IDD) is closely associated with low back pain, but its underlying mechanism remains unclear. Cholesterol is an essential nutrient in mammalian cells. Alterations in cholesterol levels lead to impairments in cell physiology, such as cell proliferation and signal transduction. Previous clinical studies demonstrated that hypercholesterolemia could be a potential risk factor for IDD, but how cholesterol induces IDD remains unknown. The current study aimed to explore the regulatory role of cholesterol in IDD development and the potential underlying mechanisms. It was found that different forms of cholesterol levels were elevated in degenerative nucleus pulposus (NP) tissues in both humans and Sprague–Dawley rats. Rats fed a high cholesterol diet (HCD) exhibited degenerative features in the lumbar intervertebral disc compared with those fed a standard diet. Interestingly, this effect could be abolished by cholesterol-lowering drug atorvastatin. In NP cells treated with TNF-α and IL-1β, a significantly higher level of cholesterol was observed. These results suggested a pivotal role of cholesterol in the progression of IDD. We also observed accelerated pyroptosis in NP cells and extracellular matrix (ECM) degradation in the rat NP cells treated with exogenous cholesterol. We further demonstrated that endoplasmic reticulum stress was responsible for cholesterol-induced pyroptosis and ECM degradation. Moreover, RNA-seq analysis revealed that the mature form of SREBP1 (mSREBP1), an important regulator of lipid metabolism, is involved in regulating endoplasmic reticulum stress in knockdown experiments. In conclusion, this study demonstrated that cholesterol could induce pyroptosis in NP cells and ECM degradation by activating endoplasmic reticulum stress through stimulating mSREBP1 in IDD.